Dysregulation of the Excitatory Renal Reflex in the Sympathetic Activation of Spontaneously Hypertensive Rat - Ye, Chao; Zheng, Fen; Wang, Jing-Xiao; Wang, Xiao-Li; Chen, Qi; Li, Yue-Hua; Kang, Yu-Ming; Zhu, Guo-Qing (Frontiers in Physiology, 2021)
Excessive sympathetic activation plays crucial rules in the pathogenesis of hypertension. Renal Chemical stimulation of renal afferents increases sympathetic activity and blood pressure in normal rats. This study investigated the excitatory renal reflex (ERR) in the development of hypertension in spontaneously hypertensive rat (SHR). Experiments were performed in Wistar-Kyoto rat (WKY) and SHR aged at 4, 12 and 24 weeks under anesthesia. Renal infusion of capsaicin was used to stimulate renal afferents, and thus to induce ERR. The ERR was evaluated by the changes in contralateral renal sympathetic nerve activity and mean arterial pressure. At the age of 4 weeks, the early stage with slight or moderate hypertension, the ERR was enhanced in SHR compared with WKY. The pressor response was greater than the sympathetic activation response in the SHR. At the age of 12 weeks, the development stage with severe hypertension, there was no significant difference in the ERR between WKY and SHR. At the age of 24 weeks, the later stage of hypertension with long-term several hypertension, the ERR was attenuated in SHR compared with WKY. On the other hand, the pressor response to sympathetic activation due to the ERR was smaller at the age of 12 weeks and 24 weeks than those at the age of 4 weeks. These results indicate that ERR is enhanced in the early stage of hypertension, and is attenuated in the later stage of hypertension in SHR. Abnormal ERR is involved in the sympathetic activation and the development of hypertension.